2010
DOI: 10.1007/s11746-010-1604-z
|View full text |Cite
|
Sign up to set email alerts
|

Blooming in Cocoa Butter Substitutes Based Compound Chocolate: Investigations on Composition, Morphology and Melting Behavior

Abstract: To provide a comprehensive analysis on the development of bloom on cocoa butter substitutes based compound chocolate, the morphology, chemical composition and melting behavior were examined. Atomic force microscopy (AFM), scanning electric microscopy (SEM), and polarized light microscopy (PLM) measurements were carried out to study the morphological properties of chocolate. AFM analyses showed a crystal growth which was confirmed by using PLM. SEM revealed that the crystal network of fresh chocolate disappeare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 19 publications
0
23
0
3
Order By: Relevance
“…These explained that higher CBS in milk chocolate required a longer time to melt than pure milk chocolate that has fully CB. 23 Wang et al 23 found that eutectic effect existed, and Tend ranged from 40 to 45°C in the mixture of CB and CBS. This finding indicates the importance of the different components of CB and CBS in milk chocolate and how it can be fully exploited for application in milk chocolate.…”
Section: Melting Characteristics Of Chocolate Compoundmentioning
confidence: 99%
See 1 more Smart Citation
“…These explained that higher CBS in milk chocolate required a longer time to melt than pure milk chocolate that has fully CB. 23 Wang et al 23 found that eutectic effect existed, and Tend ranged from 40 to 45°C in the mixture of CB and CBS. This finding indicates the importance of the different components of CB and CBS in milk chocolate and how it can be fully exploited for application in milk chocolate.…”
Section: Melting Characteristics Of Chocolate Compoundmentioning
confidence: 99%
“…The ratio 100: 0 (CBS:CB) contain about 40% of lauric acid and about 10% of palmitic acid in CBS made from hydrogenated palm kernel oil (HPKO). 23,31,32 Although CBS contains a high level of lauric and myristic acid, it is widely used as a suitable raw material in confectionery. 33 Therefore, the compound milk chocolate containing 20% CBS and 80% CB (20:80) shows similar fatty acids composition as pure milk chocolate.…”
mentioning
confidence: 99%
“…This process, however, has always been regarded to produce trans-fatty acids that increase undesirable low-density lipoprotein cholesterol [16]. Therefore, many studies have been performed to produce for CBS-based compound chocolates and coatings by blending different proportions of palm kernel oil, palm kernel stearin, palm oil or cocoa butter [6,11,17,18]. Vereecken et al studied the crystallization behavior, microstructure and macroscopic properties of the lauric-based and palm-based fats for confectionery fillings [19].…”
Section: Introductionmentioning
confidence: 99%
“…When with CB, below the limits of solubility for CBS/CB, the fats were compatible (addition 5% CB to HPKO compound chocolates) and bloom rate was slightly increased; but above this concentration (addition 5% CB to HPKS compound chocolates) the fats were incompatible and serious eutectic effects were existed. Thus, the bloom rate was significantly increased due to these phase separation, and fat migrated to the surface and then re‐crystallized into more stable forms as previous research report 3, 15. The ternary systems showed a more complex interaction because both eutectic and dilution effect were co‐existed which leaded to crystal demixion 6.…”
Section: Resultsmentioning
confidence: 78%